2019
DOI: 10.1038/s41467-019-09389-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon regulates the intratumoural environment to enhance hypoxia-based agent efficacy

Abstract: Hypoxia-based agents (HBAs), such as anaerobic bacteria and bioreductive prodrugs, require both a permeable and hypoxic intratumoural environment to be fully effective. To solve this problem, herein, we report that perfluorocarbon nanoparticles (PNPs) can be used to create a long-lasting, penetrable and hypoxic tumour microenvironment for ensuring both the delivery and activation of subsequently administered HBAs. In addition to the increased permeability and enhanced hypoxia caused by the PNPs, the PNPs can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 61 publications
(43 reference statements)
5
65
0
Order By: Relevance
“…In our study, PLGA NPs coloaded with 5Fu and PFC showed additive antitumor effects against colon cancer, which was likely due in part to PFC-mediated diffusion of oxygen into the tumor tissue. These findings agreed with previous studies that PFC could inhibit intratumoral hypoxia [29,30].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, PLGA NPs coloaded with 5Fu and PFC showed additive antitumor effects against colon cancer, which was likely due in part to PFC-mediated diffusion of oxygen into the tumor tissue. These findings agreed with previous studies that PFC could inhibit intratumoral hypoxia [29,30].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, dualloaded PLGA NPs encapsulating 5FU and PFC had the combinative antitumor effects on colon cancer, likely owing to that PFC in the tumor altered the diffusion status of the oxygen in tumor tissue. This was in agreement with the existing researches that PFC had great potential for enhancing intratumoral hypoxia [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, dual-loaded PLGA NPs encapsulating 5FU and PFC had the combinative antitumor effects on colon cancer, likely owing to that PFC in the tumor altered the diffusion status of the oxygen in tumor tissue. This was in agreement with the existing researches that PFC had great potential for enhancing intratumoral hypoxia [30,31].…”
Section: Discussionsupporting
confidence: 93%